2001
DOI: 10.1094/cchem.2001.78.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Molecular Weight (HMW) and Low Molecular Weight (LMW) Glutenin Subunits Controlled by Glu‐1 and Glu‐3 Loci on Durum Wheat Quality

Abstract: The progenies of four intervarietal durum wheat crosses were used to determine the effects of glutenin variants coded at Glu‐1 and Glu‐3 loci on durum wheat quality properties. The F2 lines were analyzed for high molecular weight (HMW) and low molecular weight (LMW) glutenin composition by electrophoresis. Whole grain derived F3 and F4 samples were analyzed for vitreousness, protein, and dry gluten contents, gluten index, SDS sedimentation volume, mixograph, and alveograph properties. Allelic variation at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
51
3
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 19 publications
16
51
3
5
Order By: Relevance
“…Genotypes, whereas the lowest score (2) was recorded for the cultivar , which was the only cultivar with the subunit 6 + 8 on the Glu-B1 locus. Similar results were also obtained by He et al (1999), Brites and Carrillio (2001) and Gálová et al (2002).…”
Section: Resultssupporting
confidence: 91%
“…Genotypes, whereas the lowest score (2) was recorded for the cultivar , which was the only cultivar with the subunit 6 + 8 on the Glu-B1 locus. Similar results were also obtained by He et al (1999), Brites and Carrillio (2001) and Gálová et al (2002).…”
Section: Resultssupporting
confidence: 91%
“…At Glu-B1, the most frequent alleles were d (6+8) and e (20x+20y) in agreement with Brites et al (1996), Igrejas et al (1999) and Raciti et al (2003). Other studies have shown negative effects of Glu-B1e on quality Turchetta et al, 1995;Brites and Carrillo, 2001). At Glu-A3, alleles a and e were the most frequent in our collection, while b and h were more widespread in germplasm from other Mediterranean countries (Igrejas et al, 1999;Moragues et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…turgidum in our germplasm (Table 2). Several studies Turchetta et al, 1995;Brites and Carrillo, 2001) have shown the better quality associated with the presence of an encoded subunit at this locus. At Glu-B1, the most frequent alleles were d (6+8) and e (20x+20y) in agreement with Brites et al (1996), Igrejas et al (1999) and Raciti et al (2003).…”
Section: Discussionmentioning
confidence: 98%
“…In Table 1, the composition of the most determinant loci in the quality of bread and durum wheat is presented. Some of these varieties have been previously studied by Igrejas et al (1999) and Brites et al (2000) and the composition here presented is in agreement with those studies. In what concerns bread wheat varieties, Almansor performs better than Pirana because it has HMW-GS of superior quality on Glu-D1 and Glu-A1 loci.…”
Section: Allelic Composition At Glutenin Locisupporting
confidence: 90%